Peningkatan Hasil Belajar PAI Siswa Kelas VIII H dengan Metode Konstruktivistik di SMPN 3 Jombang - Ariswanto, Muhamad; Darmawan, Moh. Faridl; Nasrulloh, M. Farid (YASIN, 2025)
The main issue addressed in this study is the low learning outcomes of Class VIII H students at SMPN 3 Jombang in the 2024/2025 academic year in the subject of Islamic Religious Education (Pendidikan Agama Islam/PAI), primarily due to the dominance of lecture-based, teacher-centered methods that hinder active student participation in the learning process. This study aims to improve learning outcomes through the implementation of a constructivist teaching method based on problem-based learning (PBL). The approach used is Classroom Action Research (Penelitian Tindakan Kelas) conducted in three stages: pre-test, implementation of the constructivist method, and post-test, involving 32 students as subjects. The results show a significant increase in learning mastery, from 69% of students achieving scores above the Minimum Mastery Criteria (Kriteria Ketuntasan Minimal/KKM) with an average score of 87.18 in the pre-test, to 97% in the post-test with an average score of 92.37. This improvement reflects the effectiveness of the constructivist method in fostering understanding and active student engagement in PAI learning. The study implies that integrating a constructivist, problem-based learning model into PAI instructional strategies can enhance student learning outcomes and promote more meaningful and contextual learning experiences.